2016
DOI: 10.1515/sgem-2016-0012
|View full text |Cite
|
Sign up to set email alerts
|

The influence of normal fault on initial state of stress in rock mass

Abstract: Determination of original state of stress in rock mass is a very difficult task for rock mechanics. Yet, original state of stress in rock mass has fundamental influence on secondary state of stress, which occurs in the vicinity of mining headings. This, in turn, is the cause of the occurrence of a number of mining hazards, i.e., seismic events, rock bursts, gas and rock outbursts, falls of roof. From experience, it is known that original state of stress depends a lot on tectonic disturbances, i.e., faults and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 6 publications
0
12
0
1
Order By: Relevance
“…The second type of specific infrastructure elements are tunnels, in which the railway surface also affects the structure of tunnel facility. Problems related to the exploitation of the surface in tunnels were described in [32].…”
Section: Literature Reviewmentioning
confidence: 99%
“…The second type of specific infrastructure elements are tunnels, in which the railway surface also affects the structure of tunnel facility. Problems related to the exploitation of the surface in tunnels were described in [32].…”
Section: Literature Reviewmentioning
confidence: 99%
“…ey determined at what W/H ratio and interface friction the mode of failure changes from violent to nonviolent [8]. Tajduś et al determined the effect of friction coefficient on the state of stress, which occurs in the vicinity of a normal fault [9]. Ito et al revealed the mechanism of fault slip-weakening frictional behavior [10].…”
Section: Introductionmentioning
confidence: 99%
“…New types of bolt support constructions are designed to absorb an increasing amount of energy and to better cooperate with the rock mass. With regard to the mechanism of taking over the loads, bolt supports can be divided into 3 types ( [6]- [8], [10], [11], [13], [15], [18], [19], [24], [26]). a) rigid bolts -with sufficient strength, undergoing damage when there is a load close to the breaking of the rod bolt, characterized by a small possibility of deformation, b) yielding bolts -capable of moving large deformation but having low load-bearing capacity, c) absorbing bolts -characterized by a high load carrying capacity and the ability to transfer large displacements and deformations.…”
Section: Introductionmentioning
confidence: 99%